P–757 The risk of aspirin and prednisone using in women with antithyroid antibodies undergoing assisted reproductive technology. (6th August 2021) - Xie, J; Zhou, P; Yu, Y; Chen, J; Zhou, L; Yang, L; Zou, L; Feng, C; Jin, M
Abstract: Study question: Is it safe using aspirin (A) and prednisone (P) before pregnancy among women with antithyroid antibodies (ATAbs) undergoing assisted reproductive technology? Summary answer: Combination therapy of aspirin and prednisone didn't improve likelihood of clinical pregnancy, but increased miscarriage rate. What is known already: Compared with women with negative-ATAb, women with positive-ATAb had a lower live birth rate and a higher miscarriage rate. Insufficient evidence existed to determine whether aspirin and prednisone therapy improved the success of pregnancy following assisted reproductive technology (ART) in ATAb-positive euthyroid women. Aspirin and prednisone were used frequently in clinical practice, but the use of these medicines before pregnancy during ART process is still controversial, and the risks of these medicines were not well understood. Study design, size, duration: A prospective study involving 268 women with unexplained reason for infertility who tested positive for antithyroperoxidase antibody (TPOAb) and/or thyroglobulin antibody (TgAb) were being treated for infertility at the Second Affiliated Hospital of Zhejiang University School of Medicine, Ningbo Women and Children's Hospital and People's Hospital of Jinhua from October 2017 to July 2020. Their TSH level ranged from 0.35–4.0mIU/ml and they all underwent fresh embryo transfer. Participants/materials, setting, methods: Overall, a total of 268 ATAb-positive women were divided 2 groups: group A: no treatment; B: A+P. Both medicines were used in the lowest effective dose. Between the two groups, we measured oocytes retrieved, fertilization rate, high-quality embryo rate, blastulation rate, cleavage rate, implantation rate, likelihood of clinical pregnancy and miscarriage rate. Kruskal-Wallis test was used in nonnormally distributed variables, and the χ2 test or Fisher exact test was used to compare categorical variables. Main results and the role of chance: A total of 268 infertile women with unexplained reason who tested positive for TPOAb and/or TgAb were recruited in our study. According to assignment, they were divided into two groups. All women in different groups had the similar age, BMI, number of miscarriage and duration of infertility. Levels of FSH, AMH, TSH, FT4, FT3, fibrinogen and d-dimer were similar in all groups. The use of A+P reduced cleavage rate (F = 23.982, P < 0.001) and implantation rate (F = 4.388, P = 0.036). The fertilization rate (P = 0.407), high-quality embryo rate (P = 0.208) and blastulation rate (P = 0.157) were not influenced by the use of medication. In this study, likelihood of clinical pregnancy (P = 0.066) did not change significantly after therapy, and miscarriage rate (P = 0.042) increased after medical treatment. Limitations, reasons for caution: Firstly, Aspirin is just one representation of anticoagulation therapy, so additional consideration of low molecular heparin should also be considered. Secondly, further randomized controlled trials of aspirin and prednisone alone are needed. Wider implications of the findings: In this study, use of A+P showed no positive effect, and reduced cleavage rate and implantation rate, while increased miscarriage rate. So, the use of medication for interfile women should be cautious. Trial registration number: n/a